2008
DOI: 10.1007/s00280-008-0856-x
|View full text |Cite
|
Sign up to set email alerts
|

Carboplatin dosing in overweight and obese patients with normal renal function, does weight matter?

Abstract: Purpose The purpose of this study was to determine the potential utility of alternative weight descriptors in the Cockcroft-Gault equation to more accurately predict carboplatin clearance in underweight, normal weight, overweight and obese patients.Methods Clearance values obtained from individual fits using NONMEM were compared to predicted carboplatin clearances calculated using the modified Calvert formula in which creatinine clearance was calculated with the Cockcroft-Gault equation using diverse weight de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 26 publications
2
48
0
Order By: Relevance
“…This paucity of reliable data, at least in part, ascribed to the fact that drug development and clinical trials in oncology are generally conducted irrespective of patients' body weight, and obesity is a covariate not usually stratified in data analysis. Still, it is generally acknowledged that there are considerable alterations in the pharmacokinetics of some cytotoxic drugs in obesity, which might even lead to increased toxicity but the available data are somewhat contradictory [4][5][6]. Thompson et al [7] found no differences in pharmacokinetics of daunorubicin between obese and non-obese patients while obesity worsen outcome of patients with breast cancer on doxorubicin (chemical structure is very close to daunorubicin) + cyclophosphamide therapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This paucity of reliable data, at least in part, ascribed to the fact that drug development and clinical trials in oncology are generally conducted irrespective of patients' body weight, and obesity is a covariate not usually stratified in data analysis. Still, it is generally acknowledged that there are considerable alterations in the pharmacokinetics of some cytotoxic drugs in obesity, which might even lead to increased toxicity but the available data are somewhat contradictory [4][5][6]. Thompson et al [7] found no differences in pharmacokinetics of daunorubicin between obese and non-obese patients while obesity worsen outcome of patients with breast cancer on doxorubicin (chemical structure is very close to daunorubicin) + cyclophosphamide therapy [8].…”
Section: Introductionmentioning
confidence: 99%
“…If the patient is overweight or obese (BMI ≥ 25), an adjusted body weight (ABW) should be used. 12,13 Although a number of different formulae for calculating ABW are available, the most commonly used formula is: ABW = [(Actual Body Weight -Ideal Body Weight) (0.4)] + Ideal Body Weight. Ideal Body Weight (IBW) is most commonly calculated as 14 : IBW = 50 kg + 2.3 kg/inch > 60 inch (Men); IBW = 45.5 kg + 2.3 kg/inch > 60 inch (Women).…”
Section: If the Patient Is Not Obese (Body Mass Index [Bmi]mentioning
confidence: 99%
“…Thequestionofanadequateweightdescriptorinequations including weight to estimate the carboplatin dose in overweightorobesepatientswithnormalrenalfunctionshouldbe addressednotonlyinadults [26]butalsoinchildren. Thecalculationsforpatientsofabnormalbodybuilddone inthisstudy,whilepossiblyusefulasanindicativetool,areof uncertain predictivity in the individual patient; in high-risk patients,anexactmeasureoftheGFRisessentialandshould becomplementedbytherapeuticdrugmonitoring.…”
Section: Impact Of Body Buildmentioning
confidence: 99%